Ultrasonic, volumetric and Viscometric Studies of Trichloroacetic acid-Nitrobenzene-Ethanol Solutions at Different Temperatures - Nikam, P.S.; Hiray, A.R. (Asian Journal of Chemistry, 2010)
Ultrasonic velocity, density and viscosity of trichloroacetic acid (TCAA) solutions in 0, 20, 40, 60, 80 and 100 wt% ethanol-nitrobenzene have been determined at 298.15, 303.15, 308.15 and 313.15 K. The viscosity B coefficient, limiting partial molar volume (V20) and limiting apparent molar compressibility (ɸk0) throw light on the type of solute-solvent interaction in solution.